INTERVIEW OF CHIEF EDITOR OF SCIENTIFIC AND TECHNICAL JOURNAL «CASTING AND METALLURGY», CHAIRMAN OF COUNCIL OF BELORUSSIAN PUBLIC ASSOCIATION OF FOUNDERS AND METALLURGISTS, LAUREATE OF STATE-PRIZE OF RB, DOCTOR OF TECHNICAL SCIENCES, PROFESSOR D. M. KUKUJ WITH DIRECTOR SSI IMT OF NAS OF BELARUS E. I. MARUKOVICH - D. M. Kukuj; E. I. Marukovich (Литьë и металлургия)
.